Adaptive antennas and phased arrays for radar and communications - Fenn, A. J. (Alan Jeffrey), 1953- (Artech House radar library., 2008)
Based on the author's extensive research at MIT Lincoln Laboratory, this authoritative resource offers an in-depth description of adaptive array design, emphasizing the RF characteristics, mutual coupling among elements, and field testing methods. It provides you with proven techniques for challenging projects involving radar, communication systems and antenna design. For the first time in any book, you find design guidance on specialized types of arrays, using monopole radiating elements, slotted cylinders and ultrawideband dipoles. Moreover, this unique book presents a focused near-field technique that quantifies the far-field performance of large aperture radar systems and communication systems. The book presents example prototype phased array antennas, including discussions on monopole phased arrays, finite and infinite array analyses, measurements for planar arrays of monopole elements. Further, you get a detailed explanation of focused near-field polarization characteristics of monopole arrays as related to adaptive array testing in the near field. From the fundamentals of adaptive antennas and degrees of freedom for multiple beam antennas and phased arrays ... to a test bed monopole phased array and the planar near field testing technique ... to arrays of horizontally polarized loop-fed slotted cylinder antennas and ultrawideband dipole arrays, this comprehensive book offers you invaluable, hands-on knowledge for your work in the field.